2017
DOI: 10.1039/c7cp04384h
|View full text |Cite
|
Sign up to set email alerts
|

Preferential adsorption of the additive is not a prerequisite for cononsolvency in water-rich mixtures

Abstract: Cononsolvency of poly(N-isopropylacrylamide) (PNIPAM) gels in binary mixed solvents (water-acetone and water-DMSO) has been comparatively investigated by H HR-MAS NMR spectroscopy. The results demonstrate that, although the addition of both acetone and DMSO gives rise to cononsolvency behavior, PNIPAM preferentially interacts with acetone rather than DMSO in a water-rich regime, regardless of whether the temperature is above or below the volume phase transition temperature (VPTT). It suggests that the preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 63 publications
1
40
0
Order By: Relevance
“…It should be highlighted that earlier works also showed that the preferential cosolventmonomer drives co-non-solvency (107,108). A more recent work, however, also emphasized that the preferential cosolvent-monomer binding is not a prerequisite for co-non-solvency (109) As it turned out the preferential binding of one of the solvents to the polymer is driving the conformational transition of a polymer in mixed good solvents. This is in particularly important because if both solvents like polymer equally then only weak traces of the nonideal mixing of the solvents are left, which are not sufficient to drive segregation.…”
Section: Multiscale Simulations Complex Mixtures and Polymer In Mixed Solventsmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be highlighted that earlier works also showed that the preferential cosolventmonomer drives co-non-solvency (107,108). A more recent work, however, also emphasized that the preferential cosolvent-monomer binding is not a prerequisite for co-non-solvency (109) As it turned out the preferential binding of one of the solvents to the polymer is driving the conformational transition of a polymer in mixed good solvents. This is in particularly important because if both solvents like polymer equally then only weak traces of the nonideal mixing of the solvents are left, which are not sufficient to drive segregation.…”
Section: Multiscale Simulations Complex Mixtures and Polymer In Mixed Solventsmentioning
confidence: 98%
“…For example, the collapse of a PNIPAm in aqueous urea mixtures was shown to be driven by bridging-like hydrogen bonding of urea with two NIPAm monomers (15,35). Furthermore, there are also other works showing that bridging interactions are responsible for a polymer collapse in a mixtures of two cosolvents (36,37), while another work highlighted that the preferential binding may not be prerequisite for co-non-solvency (109).…”
Section: Competitive Displacement Of Solvent By Cosolventmentioning
confidence: 99%
“…Recent studies have also shown that preferential attraction of the cosolvent is not a prerequisite for cononsolvency. 35,36 Further, cononsolvency is absent in the case of PDEA, water and methanol mixtures even when the preferential attraction of PDEA with methanol is higher in comparison to PNiPAM. 37 Thus, it can be seen that the questions regarding the applicability of a mean-field theory are not yet resolved.…”
Section: A Backgroundmentioning
confidence: 99%
“…However, recent investigations demonstrated that the preferential affinity of the cosolvent toward PNIPAM is not a general requirement for co-nonsolvency [41,42]. Furthermore, Pica and Graziano [43] bring into question that the preferential binding of cosolvent molecules to PNIPAM is the cause of co-nonsolvency in water-methanol.…”
Section: Introductionmentioning
confidence: 99%